-: Indo - Nugroho, Handika Faqih (JOURNAL EQUITABLE, 2025)
This study examines the legal relationship between P2P Lending platforms, startup operators, and fund recipient partners. The primary issue raised is the lack of transparency and legal protection for fund recipient partners. The study employs a descriptive-analytical approach based on a literature review, including an analysis of legal documents and other supporting data. The findings reveal that P2P Lending platforms play a strategic role as mediators, infrastructure providers, and credit risk assessors, while startups are responsible for fund management and fulfilling payment obligations. Robust regulations, including personal data protection under Law No. 27 of 2022, are essential to ensure the transparency and accountability of startups as operators, P2P Lending platforms, and fund recipient partners. The study concludes that collaboration among platforms, startups, and partners, supported by adequate technology and regulations, is crucial for creating a fair and sustainable funding ecosystem